Pyogenic Pancreatic Abscess Mimicking Pancreatic Neoplasm: A Four-Case Series - Kim, Mi Jin; Seo, Euikeun; Kang, Eun Seok; Kim, Keun Mo; Oh, Young Min; Cho, Byung Ha; Kim, Hyung-Woo; Ji, Myoung Jin; Jeong, Ji Won; Park, Seon Mee (The Korean journal of gastroenterology, 2015)
A pyogenic pancreatic abscess mimicking pancreatic neoplasm in the absence of acute pancreatitis is rare. We report four patients who each presented with a pancreatic mass at the pancreas head or body without acute pancreatitis. The presenting symptoms were abdominal pain, fever, or weight loss. Abdominal CT scans showed low-density round masses at the pancreas head or body with/without lymphadenopathy. In each case, a PET-CT scan showed a mass with a high SUV, indicating possible malignancy. Comorbid diseases were identified in all patients: chronic pancreatitis and thrombus at the portal vein, penetrating duodenal ulcer, distal common bile duct stenosis, and diabetes mellitus. Diagnoses were performed by laparoscopic biopsy in two patients and via EUS fine needle aspiration in one patient. One patient revealed a multifocal microabscess at the pancreatic head caused by a deep-penetrating duodenal ulcer. He was treated with antibiotics and a proton-pump inhibitor. The clinical symptoms and pancreatic images of all the patients were improved using conservative management. Infective causes should be considered for a pancreatic mass mimicking malignancy.